2014
DOI: 10.1038/ki.2013.399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic kidney disease and uremia on hepatic drug metabolism and transport

Abstract: The pharmacokinetics of non-renally cleared drugs in patients with chronic kidney disease is often unpredictable. Some of this variability may be due to alterations in the expression and activity of extra-renal drug metabolizing enzymes and transporters, primarily localized in the liver and intestine. Studies conducted in rodent models of renal failure have shown decreased mRNA and protein expression of many members of the cytochrome P450 enzyme (CYP) gene family and the ATP-Binding Cassette (ABC) and Solute C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 51 publications
3
140
1
Order By: Relevance
“…The survey sample was not large enough to generalize, but the trend suggested that activities of CYP1A2, CYP3A4, CYP2C9, CYP2C19, CYP2D6, and P-glycoprotein may be sensitive to impaired renal function. However, it has been reported that no less than 60 currently used drugs exhibit reduced nonrenal clearance and/or increased oral bioavailability in patients with chronic kidney disease (Yeung et al, 2014).…”
Section: Evidence For Potential Phenoconversion Of Dmes In Other Inflmentioning
confidence: 99%
“…The survey sample was not large enough to generalize, but the trend suggested that activities of CYP1A2, CYP3A4, CYP2C9, CYP2C19, CYP2D6, and P-glycoprotein may be sensitive to impaired renal function. However, it has been reported that no less than 60 currently used drugs exhibit reduced nonrenal clearance and/or increased oral bioavailability in patients with chronic kidney disease (Yeung et al, 2014).…”
Section: Evidence For Potential Phenoconversion Of Dmes In Other Inflmentioning
confidence: 99%
“…This has likely improved the safety of these medications for the ESRD population, yet it remains an incomplete approach, since it does not include the hepatically metabolized medications. This oversight is significant because evidence increasingly indicates that hepatic drug metabolism and transport are reduced in patients with [14][15][16][17][18][19][20][21][22][25][26][27][28]30). Consequently, administering the full dose of a hepatically metabolized medication may place an ESRD patient at similar risk for an adverse drug event as administering the full dose of a renally eliminated medication.…”
mentioning
confidence: 99%
“…We also consider that serum concentrations and drug activity of DCV and ASV combination therapy on hemodialysis may affect the viral response. Although DCV and ASV undergo hepatic biotransformation to more polar but less pharmacologically active compounds that require intact renal function for their efficient elimination [23], it has been reported that renal impairment affects the non-renal clearance of many drugs through mechanisms that appear to include downregulation/ inhibition of cytochrome P450 activity by blood uremic components [23][24][25][26]. However, this mechanism is not clear because there is little data presented to support this conclusion.…”
Section: Discussionmentioning
confidence: 52%